Internalisasi Projek Penguatan Profil Pelajar Pancasila (P5) melalui pementasan tari Reog Ponorogo di SMA BIMA Ambulu - Anas Dwi Nur Wahyudi (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
This study aims to analyze the internalization of cultural preservation values through the Projek Penguatan Profil Pelajar Pancasila (P5) using Reog Ponorogo performances at SMA BIMA Ambulu. The research employs a qualitative approach with Peter L. Berger’s Social Construction Theory as the analytical framework. Data were collected through observation, interviews, and documentation involving students, teachers, and Reog practitioners. The findings indicate that the preservation of Reog Ponorogo is implemented through extracurricular and intracurricular activities, particularly the P5 program. Through these activities, students develop cultural awareness, a sense of responsibility, discipline, teamwork, and pride in local heritage. The process of externalization, objectivation, and internalization enables students to construct their identity as cultural preservers. This study concludes that the integration of Reog Ponorogo into educational activities effectively strengthens students’ cultural identity while supporting the preservation of local wisdom among the younger generation.
Validasi dan Finalisasi Ratna 6 Juli 2026
Keywords: Reog Ponorogo; Cultural Preservation; P5; Social Construction; Cultural Identity